2021
DOI: 10.1245/s10434-021-09720-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Smoking Status on Perioperative Morbidity, Mortality, and Long-Term Survival Following Transthoracic Esophagectomy for Esophageal Cancer

Abstract: Introduction Esophagectomy is a key component in the curative treatment of esophageal cancer. Little is understood about the impact of smoking status on perioperative morbidity and mortality and the long-term outcome of patients following esophagectomy. Objective This study aimed to evaluate morbidity and mortality according to smoking status in patients undergoing esophagectomy for esophageal cancer. Methods Consec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…15 Pre-operative 'prehabilitation', optimisation of nutrition and smoking cessation have also been considered as opportunities to minimize postoperative morbidity in patients with oesophageal cancer. 16,17,18 Given 14% of patients were current smokers at time of surgery, interventions to aid smoking cessation may aid to modify morbidity of the operation. Ultimately, further studies on the feasibility of perioperative interventions to reduce complications is indicated.…”
Section: Discussionmentioning
confidence: 99%
“…15 Pre-operative 'prehabilitation', optimisation of nutrition and smoking cessation have also been considered as opportunities to minimize postoperative morbidity in patients with oesophageal cancer. 16,17,18 Given 14% of patients were current smokers at time of surgery, interventions to aid smoking cessation may aid to modify morbidity of the operation. Ultimately, further studies on the feasibility of perioperative interventions to reduce complications is indicated.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the absence of a previous history of smoking has been shown to reduce the incidence of postoperative lung disease. Smoking is also considered to be a risk factor for morbidity after esophagectomy, especially in cases involving pulmonary complications (34,35). In clinical practice, ECSS patients with these high-risk factors should be identified, and a more comprehensive treatment plan should be developed for such patients.…”
Section: Discussionmentioning
confidence: 99%
“…For squamous cell carcinoma, this may be explained by its underlying pathogenesis, wherein major etiological factors are tobacco smoking and alcohol consumption—which also act synergistically—and poor diet [ 27 ]. It has previously been reported that these patients have a higher preoperative risk profile, e.g., due to a poorer nutritional status and poorer pulmonary function, thereby increasing the risk of postoperative morbidity in these patients [ 27 , 28 , 29 ]. Although data on the extent of smoking (pack years) and the exact amount of alcohol consumption in this current cohort was limited, there was no significant association between SCC and a higher preoperative risk profile (i.e., smoking, alcohol consumption, obesity, comorbidity), as shown in Supplementary Table S5 .…”
Section: Discussionmentioning
confidence: 99%